PENERAPAN PENDEKATAN PMRI DALAM MENENTUKAN KELILING DAN LUAS LINGKARAN PADA SISWA SDI AL -MADINAH KOTA KEDIRI - Moh. Nizar Nasrodin Salim; Al-Amin (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to describe the application of the Indonesian Realistic Mathematics Approach (PMRI) in calculating the circumference and area of a circle among pupils at SDI Al-Madinah in Kediri City. This study employs a descriptive qualitative approach, focusing on depicting the learning process and pupils’ understanding of the concepts of the area and circumference of a circle. The subjects in this study were 20 Year 5 pupils at SDI Al-Madinah in Kediri City, who were then divided into four learning groups to facilitate the implementation of PMRI-based learning activities. The research data were obtained from interviews and the results of the Pupil Worksheets (LKPD) compiled using contextual problems or everyday life situations. Subsequently, the collected data were analysed descriptively to obtain an overview of the students’ ability to understand the concepts of the area and circumference of a circle. The technique used to verify the validity of the research data employed methodological triangulation by comparing the data obtained from the interviews with the students’ work on the LKPDs. The research results indicate that Year 5 pupils at SDI Al-Madinah in Kediri City were able to solve contextual problems relating to the area and circumference of a circle correctly and accurately. The students were also able to write down the steps for solving the problems systematically in accordance with the concepts they had learnt. Furthermore, based on the interview results, the students were able to explain the concepts of the area and circumference of a circle and relate them to real-world problems found in the worksheets. These findings indicate that learning that utilises PMRI-based activities and media can strengthen students’ understanding of mathematical concepts. In addition to improving understanding of the subject matter, the use of PMRI-based contextual worksheets also makes the learning process more enjoyable and meaningful, whilst enhancing students’ motivation and active participation in classroom learning activities.